Development of the Sericulture Industry in Huicheng Basin by Using Climate Resources - Chen, Jianxiong; Wu, Zhaoxia; Xu, Yuliang (Meteorological and environmental research, 2013)
Light, heat and water resources in Huicheng Basin had significant advantages, and Huicheng Basin was an ideal area for planting mulberry and breeding silkworm. Climate was mild and humid in the basin, and frost-free period was long, which provided favorable condition for planting mulberry and breeding silkworm. Main meteorological disasters affecting mulberry growth included late frost in spring, drought in end spring and early sum- mer. Continuous rain in autumn had certain influence on sericulture, but was favorable for mulberry wintering and growth in opting. At present, carrying capacity of the silkworm in the basin also had large space, and planting mulberry and breeding silkworm had wide developing prospect.